Maritime Insurgency - Asal, Victor (Terrorism and political violence, 2022)
Why do some insurgent organizations launch maritime attacks? To examine why organizations would engage in this behavior we draw on a new dataset of insurgencies to investigate the organizational characteristics associated with maritime attacks. We find that there are two types of maritime attacks by insurgencies. While both types of attacks are associated with the trappings of a state, beyond those factors, maritime revenue-raising attacks take place in a milieu of criminal activity, while maritime non-revenue-raising attacks are associated with an insurgency’s organizational sophistication and capacity.